THE IMAGE OF SAIDA IN ABDULLA KHAHHOR’S STORY “SINCHALAK” (The Conference Hub, 2025)
This article discusses the image of Saida in Abdulla Khahhor’s story “Sinchalak”. Although she is fragile, she has the strength and energy to lift the sky, and the heroine of the work, who summarizes the characteristic and typical qualities of modern progressive Uzbek women, is analyzed.